Kepuasan konsumen dalam Loyalitas Mahasiswa pengguna Maxim - M., Julianto; Suarni, Wa Ode; Pambudhi, Yuliastri Ambar (Jurusan Psikologi FKIP Universitas Halu Oleo, 2024)
Abstract Loyalty is the commitment of consumers to expressing feelings honestly toward services. One of the factors that influence consumer loyalty is customer satisfaction in using a service. Loyalty is influenced by satisfaction, where existing customer satisfaction will produce benefits for service in the form of loyalty so that good loyalty is formed. Thus satisfaction has a good effect or influence on loyalty. This study aims to determine whether consumer satisfaction plays a role in loyalty. The method used in this study is a quantitative method with an ex-post facto research design. The sample for this study was 65 respondents who were taken using the total sampling technique with the subject criteria using Maxim at the Department of Physical Education and UHO rek. The Instruments Scale of consumer satisfaction and consumer loyalty is used to collect research data. Data were analyzed by simple regression analysis. The results of this study indicate that consumer satisfaction plays a role in consumer loyalty with Maxim users with an effective contribution of 9.4 percent